Adapting Action Learning Strategies to Operationalize Reflection in the Workplace. Issue 3 (August 2020) - Faller, Pierre; Marsick, Victoria; Russell, Cynthia
The Problem: Organizations and human resources development (HRD) leaders are challenged to rethink and adapt learning and development strategies to address current and future needs. Yet, performance demands—as well as limited space, time, and resources—mean employees need to learn on their own. Not everyone knows how to do that well. The question arises: How can HRD better support employee learning? The Solution: Reflective learning practices based on action learning (AL) support work-based learning. AL "tools" help peers learn by working together in diverse groups of nonexperts on real tasks to gain new perspectives and learn to frame and solve challenges. The Stakeholders: This article shows, through a review of existing reflective processes and tools, how HRD practitioners can adapt these practices to help groups of peers and teams learn while working, to support the organization and its members in fast-changing environments.